2014
DOI: 10.1371/journal.pone.0088888
|View full text |Cite
|
Sign up to set email alerts
|

The General Composition of the Faecal Virome of Pigs Depends on Age, but Not on Feeding with a Probiotic Bacterium

Abstract: BackgroundThe pig faecal virome, which comprises the community of viruses present in pig faeces, is complex and consists of pig viruses, bacteriophages, transiently passaged plant viruses and other minor virus species. Only little is known about factors influencing its general composition. Here, the effect of the probiotic bacterium Enterococcus faecium (E. faecium) NCIMB 10415 on the pig faecal virome composition was analysed in a pig feeding trial with sows and their piglets, which received either the probio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 48 publications
6
26
1
Order By: Relevance
“…These results were consistent with abundant virus genera described in the literature (Sachsenroder et al 2014). However, we failed to identify pig stool-associated small circular DNA virus in dataset 5 (Table 4).…”
Section: Virome Analyses Using Elm With Blastn Virusessupporting
confidence: 93%
See 2 more Smart Citations
“…These results were consistent with abundant virus genera described in the literature (Sachsenroder et al 2014). However, we failed to identify pig stool-associated small circular DNA virus in dataset 5 (Table 4).…”
Section: Virome Analyses Using Elm With Blastn Virusessupporting
confidence: 93%
“…(2) Taxonomic classification based on the LCA is performed using MEGAN under the top 10% score filter (Huson et al 2007). (Sachsenroder et al 2014), this virus is the novel pig stool-associated single-stranded DNA virus, which is not assigned to a specific genus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although subclinical infections are common, circovirus infections have been suggested to be associated with psittacine beak and feather disease, infectious chicken anemia, circovirus disease of pigeons, and the postweaning multisystemic wasting syndrome of pigs (Biagini et al, 2011). Among the metagenomic studies on fecal samples of other mammals, only one study on fecal samples of pigs showed a comparable high number of sequences from the Circoviridae family (Table 1) (Sachsenroder et al, 2014). At least five metagenomic studies did not show any circovirus sequence (Lager et al, 2012;Li et al, 2011a;Li et al, 2011b;Smits et al, 2013;van den Brand et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the virome, the results show the same trends as in humans; there is predominance of bacteriophages and animal viruses more or less specific to the animal species, great diversity and concentrations one to two log units higher than for bacteria (Sachsenröder et al . ; Zhang et al . ).…”
Section: Introductionmentioning
confidence: 99%